2009
DOI: 10.1016/j.asj.2009.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Radiographic Poland Syndrome Classification: A Proposal

Abstract: Identification of the severity of PS using the proposed classification system provided an accurate study of each patient and enabled better planning for the surgical correction of functional and aesthetic deformities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 37 publications
0
7
0
2
Order By: Relevance
“…An accurate description of soft tissue and chest wall morphological abnormalities, not always easy to identify during clinical assessment, is of outstanding importance since to different types of malformation correspond a different therapeutic approach. Evaluation by US is therefore recommended (Table 3) to assess pectoralis muscle (major and minor), breast characteristics of the two halves of the thorax, and could be used as screening exam for cardiac and renal abnormalities [13]. Associated rib abnormalities are detectable by US but, when suspected, imaging work-up should be completed with other diagnostic modalities described later.…”
Section: Radiological Examinationmentioning
confidence: 99%
“…An accurate description of soft tissue and chest wall morphological abnormalities, not always easy to identify during clinical assessment, is of outstanding importance since to different types of malformation correspond a different therapeutic approach. Evaluation by US is therefore recommended (Table 3) to assess pectoralis muscle (major and minor), breast characteristics of the two halves of the thorax, and could be used as screening exam for cardiac and renal abnormalities [13]. Associated rib abnormalities are detectable by US but, when suspected, imaging work-up should be completed with other diagnostic modalities described later.…”
Section: Radiological Examinationmentioning
confidence: 99%
“…To our knowledge, less than 460 cases have been published worldwide up to now. In 2009, Ribiero RC et al suggested a clinical and radiographic classification of Poland syndrome as shown in Table II [6]. The three pathogenetic mechanisms that seem to contribute to the development of this syndrome are shown in Table III [7][8][9]].…”
Section: Discussionmentioning
confidence: 99%
“…Ipsilateral involvement of the chest muscles is the most striking hallmark, and usually presents as complete or partial agenesis of the pectoralis major, contributing to the abnormal contour of the anterior axillary border and compensatory hypertrophy of the residual synergistic muscles. 1 The insufficient arterial blood supply may also result in mammary hypoplasia; malformation of the shoulder girdle, ribs or digits; axillary alopecia; and malposition of the thoracic organs. 1 Poland syndrome is mostly benign, although there are reports of associated malignancies, including leukemia, non-Hodgkin lymphoma, and breast and lung carcinomas.…”
mentioning
confidence: 99%
“…1 The insufficient arterial blood supply may also result in mammary hypoplasia; malformation of the shoulder girdle, ribs or digits; axillary alopecia; and malposition of the thoracic organs. 1 Poland syndrome is mostly benign, although there are reports of associated malignancies, including leukemia, non-Hodgkin lymphoma, and breast and lung carcinomas. 2,3 Treatment is primarily reconstructive surgery, depending on the severity of the malformation, cosmetic appearance and functional performance.…”
mentioning
confidence: 99%
See 1 more Smart Citation